Impaired humoral immunity is associated with prolonged COVID-19 despite robust CD8 T cell responses - Lyudovyk, Olga; Kim, Justin Y; Qualls, David; Hwee, Madeline A; Lin, Ya-Hui; Boutemine, Sawsan R; Elhanati, Yuval; Solovyov, Alexander; Douglas, Melanie; Chen, Eunise; Babady, N Esther; Ramanathan, Lakshmi; et al. (Cancer cell, 2022)
How immune dysregulation affects recovery from COVID-19 infection in patients with cancer remains unclear. We analyzed cellular and humoral immune responses in 103 patients with prior COVID-19 infection, more than 20% of whom had delayed viral clearance. Delayed clearance was associated with loss of antibodies to nucleocapsid and spike proteins with a compensatory increase in functional T cell responses. High-dimensional analysis of peripheral blood samples demonstrated increased CD8 effector T cell differentiation and a broad but poorly converged COVID-specific T cell receptor (TCR) repertoire in patients with prolonged disease. Conversely, patients with a CD4 dominant immunophenotype had a lower incidence of prolonged disease and exhibited a deep and highly select COVID-associated TCR repertoire, consistent with effective viral clearance and development of T cell memory. These results highlight the importance of B cells and CD4 T cells in promoting durable SARS-CoV-2 clearance and the significance of coordinated cellular and humoral immunity for long-term disease control.